2015
DOI: 10.1177/0363546515582025
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Anterior Capsular Laxity on Horizontal Abduction and Forceful Internal Impingement in a Cadaveric Model of the Throwing Shoulder

Abstract: Increased anterior capsular laxity may exacerbate forceful internal impingement during the late cocking phase of the throwing motion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 21 publications
0
20
0
Order By: Relevance
“…Finally, a more horizontally abducted glove arm shoulder at phase 2 will cause increased external rotation moment during phase 4. While there is a known linkage between pitching shoulder horizontal abduction and external rotation moment [19], the relationship seen in this study implies that the upper trunk acts as a system. During the pitching motion, shoulder horizontal abduction between the glove arm and pitching arm appears to be an interconnected mechanism.…”
Section: Discussionmentioning
confidence: 53%
“…Finally, a more horizontally abducted glove arm shoulder at phase 2 will cause increased external rotation moment during phase 4. While there is a known linkage between pitching shoulder horizontal abduction and external rotation moment [19], the relationship seen in this study implies that the upper trunk acts as a system. During the pitching motion, shoulder horizontal abduction between the glove arm and pitching arm appears to be an interconnected mechanism.…”
Section: Discussionmentioning
confidence: 53%
“…Moreover, repetitive higher-magnitude loading of the anterior tissues of the shoulder that are associated with excessive horizontal abduction might contribute to the development of anterior shoulder instability through repeated stretching of the anterior capsular ligament based on the combination of excessive external rotation and horizontal abduction. 15,16 Although some pitchers reported that the moderate anterior shoulder laxity improves their pitching performance, 25 excessive anterior instability of the shoulder is thought to be a primary factor leading to several pitching-related shoulder injuries. 12 We demonstrated that among adolescent baseball pitchers, a higher angle of shoulder horizontal abduction at ball release was correlated most closely with the magnitude of the anterior component of the shoulder force.…”
Section: Discussionmentioning
confidence: 99%
“…The high rate of shoulder or elbow pain after Little Leaguer's shoulder might result from anterior capsular or muscular tightness, which may change shoulder biomechanics, such as humeral head position or glenohumeral translation, during throwing motion. [15][16][17][18][19] A previous 3-dimensional analysis using computed tomography showed that in baseball players with shoulder or elbow surgeries, the humerus was retroverted mainly proximally in the dominant compared with the nondominant shoulder, 12 suggesting that some of those injured baseball players might have had Little Leaguer's shoulder during elementary or junior high school.…”
Section: Discussionmentioning
confidence: 99%